The diviners - Bray, Libba (Bray, Libba. Diviners, 2013)
Seventeen-year-old Evie O'Neill is thrilled when she is exiled from small-town Ohio to New York City in 1926, even when a rash of occult-based murders thrusts Evie and her uncle, curator of The Museum of American Folklore, Superstition, and the Occult, into the thick of the investigation.